2022
DOI: 10.1002/acr.24901
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Belimumab on Organ Damage in Systemic Lupus Erythematosus

Abstract: Organ damage is a key determinant of poor long-term prognosis and early death in patients with systemic lupus erythematosus (SLE). Prevention of damage is a key treatment goal of the 2019 update of the European Alliance of Associations for Rheumatology (EULAR) recommendations for SLE management. Belimumab is a monoclonal antibody that inhibits B lymphocyte stimulator (BLyS) and is the only therapy approved for both SLE and lupus nephritis. Here, we review the clinical trial and real-world data on the effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…4,[40][41][42][43] Studies have demonstrated that biologics such as belimumab have a favorable and reliable therapeutic effect in SLE and an acceptable safety profile in long-term studies, but it is mainly works effective in patients with lupus nephritis, and its efficacy on the cardiopulmonary system is unclear. 44 Cohort studies have confirmed that the PAH Risk Stratification Scale is a good predictor of PAH regression in patients with SLE-PAH. 45 Therefore, it is recommended that patients with CTD-PAH should agree to targeted drug monotherapy or combination therapy according to PAH risk stratification, and adjusting the treatment regimen according to PAH risk stratification during regular follow-up is needed to ultimately achieve "low-risk status."…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…4,[40][41][42][43] Studies have demonstrated that biologics such as belimumab have a favorable and reliable therapeutic effect in SLE and an acceptable safety profile in long-term studies, but it is mainly works effective in patients with lupus nephritis, and its efficacy on the cardiopulmonary system is unclear. 44 Cohort studies have confirmed that the PAH Risk Stratification Scale is a good predictor of PAH regression in patients with SLE-PAH. 45 Therefore, it is recommended that patients with CTD-PAH should agree to targeted drug monotherapy or combination therapy according to PAH risk stratification, and adjusting the treatment regimen according to PAH risk stratification during regular follow-up is needed to ultimately achieve "low-risk status."…”
Section: Discussionmentioning
confidence: 87%
“…4,4043 Studies have demonstrated that biologics such as belimumab have a favorable and reliable therapeutic effect in SLE and an acceptable safety profile in long-term studies, but it is mainly works effective in patients with lupus nephritis, and its efficacy on the cardiopulmonary system is unclear. 44…”
Section: Discussionmentioning
confidence: 99%
“…In international studies, the use of belimumab in addition to standard therapy has shown promising results, with lower rates of organ damage and accrual. [68][69][70] This knowledge gap in the Asia Pacific region needs to be addressed to further understand and minimize treatment-related damage in this cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from glucocorticoids, knowledge regarding the impact of other treatments in the Asia Pacific region, including immunosuppression and biologic agents, is lacking. In international studies, the use of belimumab in addition to standard therapy has shown promising results, with lower rates of organ damage and accrual 68–70 . This knowledge gap in the Asia Pacific region needs to be addressed to further understand and minimize treatment‐related damage in this cohort.…”
Section: Discussionmentioning
confidence: 99%
“…During the past decades, much focus has been placed on clinical trials for pharmaceuticals. Despite considerable advances, the response rate to new biopharmaceuticals remains limited, and substantial proportions of patients still develop organ damage and experience severe pain, fatigue, and impaired quality of life [ 4 7 ]. The use of lifestyle changes as complementary interventions has not been thoroughly studied.…”
Section: Introductionmentioning
confidence: 99%